A preliminary survey of Trichinella spp. in pigs raised under controlled housing conditions in Colombia: 2014–2016 (2018)
ABSTRACT: A preliminary survey of Trichinella spp. infection was conducted in Colombian swine herds between 2014 and 2016. A total of 1,773 pigs reared on farms under controlled housing conditions and processed in 34 slaughterhouses were tested either by the artificial digestion of pooled muscle samples (n = 1,173) or by serology (n = 600). In addition, 550 rats trapped on 29 swine farm premises were also tested by artificial digestion. No positive pig samples were detected. Similarly, no Trichinella spp. muscle larvae were detected in rats. These results are in agreement with the lack of historical Trichinella infection reports in domestic and wild animals and humans in Colombia. However, a more extensive epidemiological investigation and a continuous surveillance program are needed to continue declaring swine herds in Colombia free of Trichinella infection.